Interpersonal communication skills in nursing - Cantos, Arthur D. (Quezon City, Philippines : C & E Publishing Inc., 2009)
Explores the dynamics of communication in the nursing process, specifically in the interview and assessment of patients, negotiation and conflict resolution, role delegation, professional assertiveness, and development and practice of critical thinking.
1. Communication skills -- 2. Assertiveness coaching -- 3. Conflict resolution -- 4. Delegation -- 5. Negotiation -- 6. Interviewing patients -- 7. Active listening -- 8. Speaking with the members of the health care team (SBAR) -- 9. Critical thinking ability.
Includes bibliographical references and index.
Keywords: CLINICAL MEDICINE